KONFLIK DAN INTEGRASI MASYARAKAT SEKITAR TAMBANG EMAS DI PAPUA, DALAM KAJIAN ANTROPOLOGI-POLITIK - Brata, Nugraha Trisnu (Faculty of Social Science, Universitas Negeri Semarang, 2010)
Various social confl icts that occur alternately with social integration is a phenomenon that oftenoccurs in the community. The reason is the existence of a confl ict of interest in the control of naturalresources. Issues raised in this study is how social confl ict and social integration that occurred in thearea around the gold mine of PT Freeport Indonesia. The purpose of this study is to inventory the casesthat occurred among local communities, migrants and companies in the Mimika district. The analysisused by Max Gluxman theory about the structure of fragmentation. Results showed that social cohesionis actually the ideal condition, if the equilibrium appears then it is only temporary. Various external andinternal confl icts that arise as result ketidakabadian equilibrium. Kamoro community united in oppositionto immigrants LEMASKO, PT Freeport and PT Jayanti. The means adopted was to protest, interceptionand hostage to the interests of these two companies’ entrants.Key words: Confl ict, integration, natural resources, fragmentation structure